Unrecognized vitamin D3 deficiency is common in Parkinson disease: Harvard Biomarker Study - Ding, Hongliu; Dhima, Kaltra; Lockhart, Kaitlin C; Locascio, Joseph J; Hoesing, Ashley N; Duong, Karen; Trisini-Lipsanopoulos, Ana; Hayes, Michael T; Sohur, U Shivraj; Wills, Anne-Marie; Mollenhauer, Brit; Flaherty, Alice W; et al. (Neurology, 2013)
To conclusively test for a specific association between the biological marker 25-hydroxy-vitamin D3, a transcriptionally active hormone produced in human skin and liver, and the prevalence and severity of Parkinson disease (PD). We used liquid chromatography/tandem mass spectrometry to establish an association specifically between deficiency of 25-hydroxy-vitamin D3 and PD in a cross-sectional and longitudinal case-control study of 388 patients (mean Hoehn and Yahr stage of 2.1 ± 0.6) and 283 control subjects free of neurologic disease nested in the Harvard Biomarker Study. Plasma levels of 25-hydroxy-vitamin D3 were associated with PD in both univariate and multivariate analyses with p values = 0.0034 and 0.047, respectively. Total 25-hydroxy-vitamin D levels, the traditional composite measure of endogenous and exogenous vitamin D, were deficient in 17.6% of patients with PD compared with 9.3% of controls. Low 25-hydroxy-vitamin D3 as well as total 25-hydroxy-vitamin D levels were correlated with higher total Unified Parkinson's Disease Rating Scale scores at baseline and during follow-up. Our study reveals an association between 25-hydroxy-vitamin D3 and PD and suggests that thousands of patients with PD in North America alone may be vitamin D-deficient. This finding has immediate relevance for individual patients at risk of falls as well as public health, and warrants further investigation into the mechanism underlying this association.